THE PROCESS IN BASUKI TJAHAJA PURNAMA’S STATEMENTS AS A VICE GOVERNOR DKI JAKARTA: FUNCTIONAL GRAMMAR APPROACH - Dwi Pebrina Sinaga; Marlina Tampubolon; Masriani Mery Rosmida Silalahi (Sean Institute, 2020)
The title of this research is The Process in Basuki Tjahaja Purnama’s Statements as A Vice Governor of DKI Jakarta: Functional Grammar Approach. In this research, the analysis is based on the theory of Functional Grammar: the transitivity, proposed by Halliday (2004) in his book; An Introduction to Functional Grammar. This research uses descriptive method. The objectives of this research are to find the types of process used by Basuki in his statements and to reveal the dominant process. The data are taken from Basuki’s statements on Liputan6.com. The result of this research shows that Material Process is dominantly used with 52,94%, followed by Relational and Existential processes with 17,65% and Mental process with 11,76%. The Material process as the dominant shows Basuki as the doer in resolving all the problems found in Jakarta